Information system for seamless positioning inside of objects under construction - Badenko Vladimir; Fedotov Alexandr; Bolsunovskaya Marina (MATEC Web of Conferences, 2018)
Methods for seamless positioning of objects inside objects under construction to ensure the implementation of the principle “always and everywhere” and achieving centimetre positioning accuracy is proposed. The current state of work on the development of experimental samples of hardware and software complexes for seamless indoor and outdoor positioning of objects is presented. It is proposed to use radio-frequency technologies to solve the problem. The main methodological approaches and their first implementations are presented. The main feature of algorithms proposed is the implementation of a seamless transition when determining the position of the object in indoor and outdoor space with usage of an inertial system and radio-frequency positioning systems (in real time regime and without real time regime).